Folate Deficiency Is Prevalent in Women of Childbearing Age in Belize and Is Negatively Affected by Coexisting Vitamin B-12 Deficiency: Belize National Micronutrient Survey 2011. Issue 6 (12th April 2017) - Rosenthal, Jorge; Largaespada, Natalia; Bailey, Lynn B; Cannon, Michael; Alverson, CJ; Ortiz, Dayrin; Kauwell, Gail PA; Sniezek, Joe; Figueroa, Ramon; Daly, Robyn; Allen, Peter
Abstract: Background: Folate deficiency, vitamin B-12 deficiency, and anemia can have adverse effects on birth outcomes. Also, low vitamin B-12 reduces the formation of metabolically active folate. Objectives: We sought to establish the baseline prevalence of and factors associated with folate deficiency and insufficiency, vitamin B-12 deficiency, and anemia among women of childbearing age (WCBA) in Belize. Methods: In 2011, a national probability-based survey was completed among Belizean nonpregnant WCBA aged 15–49 y. Blood samples for determination of hemoglobin, folate (RBC and serum), and vitamin B-12 (plasma) and sociodemographic and health information were collected from 937 women. RBC and serum folate concentrations were measured by microbiologic assay (MBA). Folate status was defined based on both the WHO-recommended radioproteinbinding assay and the assay adjusted for the MBA. Results: The national prevalence estimates for folate deficiency in WCBA, based on serum and RBC folate concentrations by using the assay-matched cutoffs, were 11.0% (95% CI: 8.6%, 14.0%) and 35.1% (95% CI: 31.3%, 39.2%), respectively. By using the assay-matched compared with the WHO-recommended cutoffs, a substantially higher prevalence of folate deficiency was observed based on serum (6.9% absolute difference) and RBC folate (28.9% absolute difference) concentrations. The prevalence for RBC folate insufficiency was 48.9% (95% CI: 44.8%, 53.1%). Prevalence estimates for vitamin B-12 deficiency and marginal deficiency and anemia were 17.2% (95% CI: 14.2%, 20.6%), 33.2% (95% CI: 29.6%, 37.1%), and 22.7% (95% CI: 19.5%, 26.2%), respectively. The adjusted geometric means of the RBC folate concentration increased significantly ( P -trend < 0.001) in WCBA who had normal vitamin B-12 status relative to WCBA who were vitamin B-12 deficient. Conclusions: In Belize, the prevalence of folate and vitamin B-12 deficiencies continues to be a public health concern among WCBA. Furthermore, low folate status co-occurred with low vitamin B-12 status, underlining the importance of providing adequate vitamin B-12 and folic acid intake through approaches such as mandatory food fortification.